Web-Based UTHM Event Management System - MARZELE, MUHAMMAD ALI UZAIR; Abdul Jalil, Rozita (Applied Information Technology And Computer Science, 2025)
Approximately 60 student clubs and organizations from Universiti Tun Hussein Onn Malaysia (UTHM) are currently officially registered. For students, Managing event applications manually is time-consuming and energy-intensive. Therefore, the objective of this project is to develop a system that effectively manages all of the data related to the multiple events the organization hosts. UTHM Event Management System (EMS) will be developed by using an object-oriented approach and using prototype model. The goal is to maintain a central MySQL database containing all event-related data. The system supports various tasks and procedures required for effective event data management. This system is being created through three iterations of the developing software prototyping model. PHP programming language is used to create a web-based UTHM EMS, which systematizes event applications and makes event administration easier. Minimum input effort and simple retrieval of data are made possible by the UTHM EMS. It helps in lowering errors brought on by human error. The system is easily accessible from any location and features user-friendly interfaces for data collection and fast information searches. To sum up, the UTHM EMS is helpful for effectively and efficiently managing information about UTHM events